Transition in the European refining sector: strategies to meet present and future industry challenges from a Central European perspective - Virag, A (Oxford Institute for Energy Studies, 2013)
The European refining industry faces a multiplicity of challenges. New legislation and growing global competition are squeezing margins. Operational and organisational efficiency will hold the key to success and survival for European refiners. Vertical integration with upstream operations and retail markets, as well as on-site horizontal integration between refineries and petrochemical plants are routes to greater resilience.